The Concept of Environment in Folktales from Different Cultures: Analysis of Content and Visuals - Ahi̇, Berat; Yaya, Dilara; Ozsoy, Sibel (International Electronic Journal of Environmental Education, 2014)
Normal 0 21 false false false TR X-NONE X-NONE MicrosoftInternetExplorer4 The aim of the study is to determine how the children’s stories, which are such powerful, handled the nature and environment through the texts, and were portrayed the concept of nature in different cultures. This study examined the texts in 15 children’s picture stories which subjected to the perception of nature and environment, published between 1989-2002 in nine different regions of the world. The research methodology for this study is content analysis that includes methods of qualitative data collection and analysis. In this research overt and covert messages are examined deeply to try to reveal the image of the nature with its causes. As result of the content analysis 15 folktales’ subjects are identified as nature-human interaction, negative attitudes towards the environment, pollution, natural life and elements of nature. Six stories focused on the interaction of nature and human beings. In general these stories are embroidered the therapeutic effect on human nature. In two tales there are messages would cause negative attitudes towards nature. The examined books present nature in different ways. In two stories there are descriptions of nature, one of them involves a number of ecological niches existing in nature, in one another story there is environmental pollution, and another story describes a day in nature. When 15 different stories which are printed in five different books’ pictures are technically examined, it’s seen that pictures of three books are painted with oil paint, and pictures of the other two books are drawn with watercolor. In general, despite the images describe a sentence in the text, fails to explain the scree-plot. So this situation makes think when children examining books on their own, understanding all of the text gets harder.
Keywords: Nature; environmental education; child stories; pictures; qualitative research; content analysis.; 13. Climate action; 4. Education; 3. Good health